2013
DOI: 10.4028/www.scientific.net/kem.554-557.204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mechanical Parameters Used as Input Data in the Yield Criteria on the Accuracy of the Finite Element Simulation of Sheet Metal Forming Processes

Abstract: The accuracy of the finite element simulation of sheet metal forming processes is mainly influenced by the shape of the yield surface used in the mechanical model and, in particular, by the number of input values used in the identification of the yield surface. This paper investigates the effect of the input values used for identifying the BBC 2005 yield criterion on the accuracy of the finite element predictions. The accuracy assessment of the simulation is based on the comparison of the numerical predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The experimental data in Table 4 yield that σ 0 =σ 90 < 1 for both SS304 and DKP6112 steels, verifying weakness of the Hill'48 model to simulate the real yield behavior of the material in the experiments. The Hill'48 model uses only the uniaxial yield stress in the rolling direction to describe the anisotropy coefficients [40,46] whereas Hu2003, Yld2003-8p and BBC2008-8p criteria use yield stresses and r-values found from uniaxial and biaxial tension tests.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental data in Table 4 yield that σ 0 =σ 90 < 1 for both SS304 and DKP6112 steels, verifying weakness of the Hill'48 model to simulate the real yield behavior of the material in the experiments. The Hill'48 model uses only the uniaxial yield stress in the rolling direction to describe the anisotropy coefficients [40,46] whereas Hu2003, Yld2003-8p and BBC2008-8p criteria use yield stresses and r-values found from uniaxial and biaxial tension tests.…”
Section: Discussionmentioning
confidence: 99%
“…Buna ek olarak Barlat-89 modeli bu prosesin şekillendirme adımını dahi tahmin edememiştir. Barlat-89 modelinin alüminyum alaşımları için daha uygun bir model olduğu literatürdeki çalışmalarla doğrulanmıştır [34,35]. Bu durum yapılan çalışmada da gözlemlenmiş olup çelik malzemelerde Barlat-89 modeli özellikle şekil bozukluğu açısından başarısız olmuştur.…”
Section: V-kalıpta Eğmeunclassified
“…Moreover, it has been shown that the ability of a yield criterion to describe the material's anisotropic behaviour depends on its flexibility, which in turn is related to the number of anisotropic parameters. As a consequence, the necessary number and type of experimental tests for the calibration of flexible yield criteria increases [13,25,26]. However, the cost associated with a large number of different types of experimental tests along with the mathematical complexity of the advanced yield criteria are the major shortcomings contributing to a limited use in an industrial environment.…”
Section: Introductionmentioning
confidence: 98%
“…The predictions obtained with BBC2005, Hill48 and Yld89 yield criteria are compared to experimental ones, showing that BBC2005 leads to the best agreement. Lazarescu et al [26] provides a rough guide, stating that the Yld89 criterion is better at predicting the biaxial yield stress than Hill48, which underestimates the experimental data for the AA6016-T4 aluminium alloy. As an alternative to the extensively used conventional calibration procedures which are based on uniaxial tensile and equibiaxial tests, Aretz put forward a calibration method involving three directional uniaxial tensile tests and two plane strain tensile tests, performed in the rolling and transverse directions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation